Planning approach of survivable fiber-wireless broadband access network - Hongjun TAN; Yamin XIE; Yejun LIU (Dianxin kexue)
The emerging fiber-wireless（FiWi）broadband access network provides not only the new technological references for flexible broadband access anywhere and anytime,but also the research opportunities for the cost-efficient design of survivable broadband access network.The study of survivable FiWi access network planning was focused on,and an approach of survivable network planning based on wireless-rerouting protection was proposed.When any fiber link cuts,the failed optical network unit（ONU）can transfer its traffic into other normal ONUs.Solving the joint optimization problem of wireless routers placement,backup radios configuration and ONU capacity allocation was put more importance on,aiming to fully protect all traffic with the minimum deployment cost.The method of integer linear programming was employed to obtain the optimal solution for small-scale network planning.The heuristic algorithm was also proposed for the large-scale network planning.Simulation results demonstrate the effectiveness of the proposed approach in reducing network deployment cost.